Dampak Pengembangan Biofuels terhadap Volatilitas Harga Beberapa Komoditas Pangan di Pasar Dunia - Sholihah, Fathimah; Kusnadi, Nunung (Jurnal Agro Ekonomi, 2019)
EnglishAgricultural product based biofuels are the connecting points of the linkages between the global agricultural commodity,  energy, and  financial markets. Since the global energy markets and financial markets are volatile in nature, rapid expansion of biofuels industry results in increasing volatility of agricultural commodity prices, particularly food prices. The aims of this research is to review price volatility of some food commodities (wheat, corn and soybean) in in the world markets and to analyze the impact of global biofuels development on the price volatility. The price volatility is analyzed using the ARIMA and ARCH GARCH methods. The results show that prices of food commodities have been more volatile since the United States of America imposed the Renewable Fuel Standard Mandate-2 policy in 2007. The Corn and soybean price volatilities are higher than rice and wheat. The stronger are their linkages with biofuels development, the higher are their price volatilities. Increasing food price volatility and level should be considered as challenges and opportunities for accelerating food production growth through technological innovation and land expansion toward the achievement food self-sufficiency such that the national food security system is resilient against global market disturbances.IndonesianBiofuels berbahan baku hasil pertanian menjadi komoditas penghubung antara pasar komoditas pertanian dengan pasar energi, dan selanjutnya dengan pasar finansial dunia. Oleh karena pasar energi dan pasar finansial dunia rentan gejolak maka pengembangan biofuel secara besar-besaran berdampak pada peningkatan volatilitas harga komoditas pertanian, utamanya komoditas pangan pokok. Penelitian bertujuan untuk meninjau volatilitas harga jagung, gandum, beras dan kedelai di pasar dunia  serta untuk menganalisis dampak pengembangan biofuels terhadap volatilitas harga tersebut. Analisis volatilitas harga dilakukan dengan metode ARIMA dan ARCH GARCH. Penelitian menunjukkan bahwa harga komoditas pangan lebih volatil setelah Amerika Serikat menerapkan kebijakan Renewable Fuels Standard Mandate-2 tahun 2007. Volatilitas harga jagung dan kedelai lebih tinggi daripada beras dan gandum. Semakin besar keterkaitan komoditas dengan pengembangan biofuels maka semakin besar pula volatilitas harga komoditas tersebut. Peningkatan volatilitas dan level harga tersebut dapat dipandang sebagai tantangan dan peluang untuk memacu peningkatan produksi pangan melalui pengembangan teknologi dan ekstensifikasi lahan pertanian guna meningkatkan kemandirian pangan  sehingga sistem ketahanan pangan nasional lebih tahan menghadapi gejolak pasar global.